PERSON DEIXIS IN CABLE NEWS NETWORK INTERNATIONAL WEBSITE - Anak Agung Istri Mas Trisnamayuni; I Nyoman Kardana; Ni Wayan Kasni (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2026)
This study analyzes the use of person deixis in news texts published on the Cable News Network (CNN) International Website. Based on Levinson’s (1983) theory of deixis, this research aims to identify the types of person deixis and determine their dominant usage in news discourse. A mixed-method approach was applied, combining qualitative descriptive analysis and quantitative frequency analysis. The data were obtained from selected CNN news articles published between August and December 2021. The findings show that third person deixis is the most dominant type, reflecting the objective and informative nature of news reporting. First person deixis appears mainly in direct quotations, while second person deixis is used in limited contexts to address readers or quoted participants. This study concludes that person deixis plays an essential role in conveying information clearly and maintaining coherence in news texts.